2004
DOI: 10.7205/milmed.169.6.433
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directives and Do-Not-Resuscitate Orders on General Medical Wards versus the Intensive Care Unit

Abstract: The records of 335 patients admitted to the general medicine wards and to the medical intensive and coronary care unit (MICCU) at Brooke Army Medical Center were retrospectively reviewed to assess the frequency of advance directives and "do not resuscitate" (DNR) designations. Two hundred sixty-seven (79.7%) were admitted to the ward and 68 (20.3%) were admitted to the MICCU. Advance directives were executed in 14.9% of patients. DNR designations were made for 21 (7.9%) patients on the ward and 11 (16.2%) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…146,147 Even in at-risk populations, such as endstage renal disease or geriatric patients, the penetration remains low. 146,[148][149][150][151] Doctors are frequently unaware of advance directives that may exist, or do not have them available when needed.…”
Section: Advance Directivesmentioning
confidence: 99%
“…146,147 Even in at-risk populations, such as endstage renal disease or geriatric patients, the penetration remains low. 146,[148][149][150][151] Doctors are frequently unaware of advance directives that may exist, or do not have them available when needed.…”
Section: Advance Directivesmentioning
confidence: 99%
“…Environmental influences on completing ADs were most often associated with the housing setting of study participants, such as completion rates among institutionalized patients (Kemp et al, 2004; Mezey et al, 2000) or community‐dwelling clients (Decker & Reed, 2005; Molloy et al, 2000). No studies were found on the influences of participating in senior centers as an environmental determinant of completion of ADs.…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive programs to implement the requirements of the law have been carried out among different healthcare agencies, and all 50 states have enacted legislation supporting ADs. Despite these efforts, many recent studies still have indicated only 20% or less of the general population have completed ADs (DeLuca Havens, 2000; Hopp, 2000; Kemp, Emmons, & Hayes, 2004; Mezey, Leitman, Mitty, Bottrell, & Ramsey, 2000, Salmond & David, 2005).…”
mentioning
confidence: 99%
“…For example, in a report of patients from an Oncology ICU, 15.7% had an advanced directive, 47.6% had a health care proxy and 36.7% had neither (Halpern et al, 2011). These frequencies were higher than those reported for two studies of Medical Intensive Care Units where only 9-15% of patients had a documented advanced directive (Baranowski-Birkmeier et al, 1995;Kemp et al, 2004). However all of these findings are considerably higher than the frequencies found in the current study.…”
Section: Discussionmentioning
confidence: 41%